2012
DOI: 10.1117/12.907433
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast magnetism as seen by x-rays

Abstract: Revealing the ultimate speed limit at which magnetic order can be controlled, is a fundamental challenge of modern magnetism having far reaching implications for magnetic recording industry. Exchange interaction is the strongest force in magnetism, being responsible for ferromagnetic or antiferromagnetic spin order. How do spins react after being optically perturbed on an ultrashort timescales pertinent to the characteristic time of the exchange interaction? Here we demonstrate that femtosecond measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
59
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 10 publications
3
59
0
Order By: Relevance
“…In other materials, such as CuO or La0.5Sr1.5MnO4, it was observed that pumping with 800 nm light leads to an ultrafast suppression of magnetic order in less than 1 ps and that the magnetic phase transformation is delayed by approximately ¼ of the period of the low lying spin gap excitation [10,12]. Such ultrafast changes in magnetization (less than 1 ps) have also been observed in metallic ferromagnets via all optical pump/probe schemes and optical pump/XMCD (X-ray magnetic circular dichroism) probe experiments [14][15][16].…”
Section: Introductionmentioning
confidence: 69%
“…In other materials, such as CuO or La0.5Sr1.5MnO4, it was observed that pumping with 800 nm light leads to an ultrafast suppression of magnetic order in less than 1 ps and that the magnetic phase transformation is delayed by approximately ¼ of the period of the low lying spin gap excitation [10,12]. Such ultrafast changes in magnetization (less than 1 ps) have also been observed in metallic ferromagnets via all optical pump/probe schemes and optical pump/XMCD (X-ray magnetic circular dichroism) probe experiments [14][15][16].…”
Section: Introductionmentioning
confidence: 69%
“…For elemental ferromagnets the emerging dynamics can be probed using conventional magneto-optical methods [1,2]. For magnets composed of several distinct elements, such as ferrimagnetic or ferromagnetic alloys, the individual spin dynamics of the different elements can be probed employing ultrafast excitation in combination with the femtosecond-resolved x-ray magnetic circular dichroism (XMCD) technique [3,4]. An astonishing example of such element-specific ultrafast magnetization dynamics was first measured on ferrimagnetic GdFeCo alloys [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been discovered that reduction of the magnetic field pulse durations below about 2-3 ps may result in a stochastic magnetization switching 4 . One of the most intriguing alternatives to magnetic field-induced magnetization switching is making use of a subpicosecond laser pulse [5][6][7][8] . Since the first observation of subpicosecond demagnetization of a Ni film subjected to a 60-fs laser pulse, it has been shown that such a pulse is able to cause ultrafast changes in the magnetic state 9 .…”
Section: Introductionmentioning
confidence: 99%